Perceptions of racism in healthcare among patients with systemic lupus erythematosus: a cross-sectional study - Vina, Ernest R (Lupus Sci Med, 2015)
BACKGROUND: Racial disparities in the clinical outcomes of systemic lupus erythematosus (SLE) exist. Perceived racial discrimination may contribute to disparities in health. OBJECTIVES: To determine if perceived racism in healthcare differs by race among patients with SLE and to evaluate its contribution to racial disparities in SLE-related outcomes. METHODS: 163 African–American (AA) and 180 white (WH) patients with SLE were enrolled. Structured interviews and chart reviews were done to determine perceptions of racism, SLE-related outcomes (Systemic Lupus International Collaborating Clinics (SLICC) Damage Index, SLE Disease Activity, Center for Epidemiologic Studies-Depression (CES-D)), and other variables that may affect perceptions of racism. Serial hierarchical multivariable logistic regression models were conducted. Race-stratified analyses were also performed. RESULTS: 56.0% of AA patients compared with 32.8% of WH patients had high perceptions of discrimination in healthcare (p<0.001). This difference remained (OR 4.75 (95% CI 2.41 to 8.68)) after adjustment for background, identity and healthcare experiences. Female gender (p=0.012) and lower trust in physicians (p<0.001) were also associated with high perceived racism. The odds of having greater disease damage (SLICC damage index ≥2) were higher in AA patients than in WH patients (crude OR 1.55 (95% CI 1.01 to 2.38)). The odds of having moderate to severe depression (CES-D ≥17) were also higher in AA patients than in WH patients (crude OR 1.94 (95% CI 1.26 to 2.98)). When adjusted for sociodemographic and clinical characteristics, racial disparities in disease damage and depression were no longer significant. Among AA patients, higher perceived racism was associated with having moderate to severe depression (adjusted OR 1.23 (95% CI 1.05 to 1.43)) even after adjusting for sociodemographic and clinical variables. CONCLUSIONS: Perceptions of racism in healthcare were more common in AA patients than in WH patients with SLE and were associated with depression. Interventions aimed at modifiable factors (eg, trust in providers) may reduce higher perceptions of race-based discrimination in SLE.